Coincidence and Common Fixed Point Theorem in Cone Metric - Badshah, V.H.; Choursiya, Swati; Gupta, Dr. V. K. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The aim of this paper is to establish a coincidence and common fixed point theorem for four self maps satisfying a contractive condition in a cone metric space. The intent of this paper is to introduce the concept of compatibility without assuming its normality.